2016
DOI: 10.1136/neurintsurg-2016-012399
|View full text |Cite
|
Sign up to set email alerts
|

Citation classics in neurointerventional research: a bibliometric analysis of the 100 most cited articles

Abstract: Our study presents a detailed list and analysis of the 100 most cited articles in the field of neurointervention and provides a historical perspective on the scientific progress in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 22 publications
7
21
0
Order By: Relevance
“…Third, our study showed that 54.5% of the most mentioned articles originated from the USA, which is in agreement with but slightly more concentrated in the USA compared with the previous citation classic study in the same field (45.0% US articles) 10. These findings prove not only scientific impact but influence beyond academia of the USA in research related to neurointervention.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Third, our study showed that 54.5% of the most mentioned articles originated from the USA, which is in agreement with but slightly more concentrated in the USA compared with the previous citation classic study in the same field (45.0% US articles) 10. These findings prove not only scientific impact but influence beyond academia of the USA in research related to neurointervention.…”
Section: Discussionsupporting
confidence: 90%
“…A previous citation classic study published in 2017 reported the 100 most cited neurointervention articles that were cited between 1912 and 170 times (mean 363.4) 10. Only five articles overlapped between the 101 most mentioned articles in our study and the 100 most cited articles in the previous work.…”
Section: Discussionsupporting
confidence: 42%
See 3 more Smart Citations